Effect of fertility associated proteins on lipid peroxidation production in Holstein Friesian semen - KRISHNAN, G; THANGVEL, A; LOGANATHASAMY, K; VEERAPANDIAN, C; KUMARASAMY, P; KARUNAKARAN, M (The Indian Journal of Animal Sciences, 2015)
Present study was designed to evaluate effects of fertility associated proteins on sperm motility, viability and level of lipid peroxidation (LPO) in semen. Holstein Friesian breeding bulls (17) were screened for fertility associated proteins (24, 28–30 and 55 kDa proteins), and categorized into 8 groups based on presence/absence in the seminal plasma and sperm membrane. Level of LPO compound malondialdehyde (MDA) was assessed in fresh and frozenthawed semen using thiobarbituric acid method. Fresh semen of bulls positive for fertility associated proteins had lower MDA (0.433±0.03 μmol/ml) than bulls negative for fertility associated proteins (0.740±0.05 μmol/ml). Level of MDA increased in frozen-thawed sperm by 1.5 fold as that of fresh semen among bulls positive for fertility associated proteins and 2 fold in negative bulls. MDA level increased by 27% in all the frozen-thawed semen incubated at 37°C for 180 min, however it was lower in bulls with fertility associated proteins (2.380±0.14 μmol/ ml) than negative bulls. Fresh semen with fertility associated proteins had higher number of motile sperm with progressive motility than negative bulls. Further, bulls with fertility associated proteins were able to sustain higher number of viable sperms with progressive motility than negative group at the end of 180 min of incubation. The results concluded that the fertility associated proteins were capable to sustain sperm viability and motility by limiting LPO production in fresh and frozen-thawed semen.